Optimal Consensus-Based Event-Triggered Control Strategy for Resilient DC Microgrids - Shi, Mengxuan; Shahidehpour, Mohammad; Zhou, Quan; Chen, Xia; Wen, Jinyu (IEEE transactions on power systems, 2021)
In this paper, an optimal consensus-based event-triggered control strategy is proposed to coordinate multiple distributed energy resources (DERs) in a dc microgrid. In the proposed control strategy, the average bus voltage restoration and the proportional current sharing are integrated by transforming the coordinated control problem into an optimization problem. The proposed solution enhances the resilience of the controller strategy in extreme events with uncertain initial states. Accordingly, the proposed control strategy provides a sampled-data-based event-triggered mechanism considering the limited availability of communication resources, which reduces communication burdens and avoids Zeno behaviors. The sufficient conditions are demonstrated using the Lyapunov-Krasovskii functional method for maintaining the stability of the proposed control strategy. Several case studies are presented using the PSCAD/EMTDC platform and the results are discussed to validate the effectiveness of the proposed control strategy for enhancing the dc microgrid resilience.